IMPLEMENTASI PENDIDIKAN KARAKTER DISIPLIN SISWA DALAM PEMBELAJARAN DARING DI KELAS IV SEKOLAH DASAR NEGERI CENGKLIK SURAKARTA TAHUN PELAJARAN 2020/2021 - Novia Putri Bertina; Sugiaryo Sugiaryo; Mukhlis Mustofa (UNIVERSITAS SLAMET RIYADI, 2022)
The aims of this study were 1) to find out the implementation of character education regarding Student discipline in online learning, 2) to find out the obstacles faced by teachers in Implementing character education about student discipline in online learning, 3) to find out what Strategies the teacher used in implementation of character education about student discipline in Online learning.The research method used was a descriptive qualitative research. The research subjects used Were students in class IV, class teacher, school principal and parents. Source of data obtained Was primary data obtained directly. Data collection techniques were through interviews, Documentation, questionnaires, and observation. The validity of the data used was the credibility Test. The data analysis technique used was descriptive qualitative with an interactive model. The results of the research were 1) the implementation of character education regarding student Discipline is always applied in every learning taking place. This implementation was carried out Using learning media such as WhatsApp, Zoom, Google Meet. 2) the obstacles faced by teacher Were students who still needed direct examples from teacher, learning that was still teacher- Centered, less optimal delivery of learning material, 3) the strategy used by teachers in Implementing character education regarding student discipline was to provide rewards for Achievement obtained by students Keywords: Discipline Character, Online Learning, Students